Design Management Accounting System for Village-Owned Enterprises - Rani Rahmawati; Salvana Anugerah Naftali; Nadifah Zukhriyah; Ignatius Oki Dewa Brata; Sendi Gunandar Arnan (Magister Akuntansi FB-UK.Maranatha, 2019)
Indonesia were country that have many village cross the country. Government policy to rise economic in the villages through Village-Owned Enterprises were brilliant idea. But in the journey many things that need be done to make Village-Owned Enterprises can perform well. One of the most important point is made or design Accounting Information System. Whit this design Accounting Information System the researcher hope can help elevate the Village-Owned Enterprises organization function better than before. Design this system use three activities cycle that use in Accounting Information System. This paper describe the researcher activities in helping Village-Owned Enterprises in North Bandung city. Keywords: Accounting, Information, System, Design, Village-Owned Enterprises